Efeito da fração aquosa de cissampelos sympodialis eichl. em artéria pulmonar de rato com hipertensão pulmonar induzida por monocrotalina - Maciel , Priscilla Maria Pereira (2015)
The pulmonary hypertension (PH) is caracterized for the increase chronic pulmonary arterial pressure, vascular remodeling and ventricle right hypertrophy. The oxidative stress is a common disorders in the PH. Cissampelos sympodialis Eichl. is frequently used in the popular medicine for the treatement of deseases of the tract respiratory, rheumatism and arthritis. Furthermore many of these activites it has been proved scientifically making this plant an promising target. In this context this study had with aim to evaluate the acute effect of aqueous fraction of Cissampelos sympodialis Eichl (FAFCS) in pulmonary artery of normotensives rats and to avaluate the FAFCS potential in to prevent and/or to improve the pulmonary vascular dysfunction induced for the monocrotaline PH (MCT). In pulmonary artery rings precontracted with phenilefrine (PHE) (1uM) isolated of normotensive rats, FAFCS (10-3000ug/mL) induzed vasorelaxation, concentration dependent, with (MR=98±2%; EC50=599μg/mL) or without of endothelium (MR=102±2%; EC50 =700μg/mL), demostrate that FAFCS produces vasorelaxation independent of the endothelial factors. The PH was induced for the subcutaneous injection of MCT (60mg/kg, single dose). The animals receive FAFCS oral via (50 ou 100mg/kg/day), sildenafil or saline during 28 days. The MCT group presented increase of PAP (63±5 mmHg) and HVD (0,52±0,03g) in comparing to the control group (PAP=29±2mmHg; HVD=0,28±0,02g). The treatment with FAFCS 50mg/kg (PAP=46±3mmHg; HVD=0,36±0,04g) and 100mg/kg (30±5mmHg; HVD=0,37±0,05g) or sildenafil 50mg/kg (32±2mmHg; HVD=0,35±0,03g) showed a significant reduction in pressure and right ventricular hypertrophy compared to the MCT group. In the tests of vascular reactivity the MCT animals showed reduction of the response to PHE (Δ contraction=0,37±0,04g) and decrease of the reponse vasorelaxation to ACh and NPS (MR=45±6%) in relation to the control group (PHE, Δ contraction=0,86±0,09 g; NPS, MR=96±6%). The treatment with FAFCS or sildenafil not reversed to endothelial dysfunction caused for the exposition to MCT. However the effect to PHE and the NPS were restored with FAFCS 50mg/kg (PHE, Δcontraction =0,63±0,04g; MR=79±3%), FAFCS 100mg/kg (PHE, Δcontraction=0,77±0,06g; NPS, MR= 85±5 %) e sildenafil (PHE, Δcontraction = 0,8±0,08g; NPS, MR=72±2%). Furthermore FAFCS reduced significantly the levels of reactive oxygen species in the DHE staining in pulmonary artery. In conclusion these results suggests that FAFCS promotes relaxant effect endothelium independent in pulmonary artery of normotensive rats. In PH monocrotaline-induced the treatment with FAFCS reduced the oxidative stress and restore the damage on smooth muscle in pulmonary artery of rat and hypertrophy right ventricle induced by monocrotaline.